Markers of NETosis Do Not Predict Neonatal Early Onset Sepsis: A Pilot Study - Stiel, Carolin U.; Ebenebe, Chinedu U.; Trochimiuk, Magdalena; Pagarols Raluy, Laia; Vincent, Deirdre; Singer, Dominique; Reinshagen, Konrad; Boettcher, Michael (Frontiers in Pediatrics, 2020)
Introduction: Early-onset sepsis in neonates potentially results in substantial morbidity and mortality. A key player in sepsis a neutrophil extracellular traps (NETs) to limit dissemination of pathogens. Aim of this study was to evaluate markers of NET formation in umbilical cord blood as a predictor of neonatal sepsis. Methods: Prospective study including term and preterm neonates. Umbilical cord blood samples were obtained immediately after birth and following markers of inflammation and NET formation were assessed: complete blood count, C-reactive protein (CRP), interleukin 6 (IL-6), levels of cell-free DNA (cfDNA), neutrophil elastase (NE), and myeloperoxidase (MPO). The study population included neonates with confirmed early-onset sepsis and propensity score matched controls. Results: Umbilical cord blood samples of 491 neonates were obtained, of whom 17 neonates (n = 17) presented clinical and laboratory signs of infection within the first 72 h postpartum. Seventeen neonates without infection were matched as controls. IL-6 differed significantly between both groups, whereas other infection parameters such as CRP and neutrophil levels, and in particular the NET surrogate markers (cfDNA, NE, MPO), did not show any significant differences. Conclusion: NET markers in umbilical cord blood appear to not predict the onset of neonatal sepsis. These findings probably result from the neonates‘ inability or delayed ability to form NETs, which is suspected to be a main reason for the increased risk of severe infections in neonates, but is also assumed to prevent negative NET-mediated consequences during perinatal adaptation.